Pengaruh Lingkungan Kerja, Disiplin Kerja dan Kerjasama Tim terhadap Kinerja Karyawan di Gtv Hotel and Apartemen di Masa Pandemi Covid-19 - Nanda Aswan Rosmana; Sri Wahyuningsih (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the effect of the work environment, work discipline and teamwork on employee performance at the GTV Hotel and Apartment. This research consists of four variables, namely Work Environment (X1), Work Discipline (X2) and Teamwork (X3) on Employee Performance (Y). This study used a sample of 75 employees. This research used data collection methods in the form of interviews, observations, questionnaires. The data analysis method used is Lisrel for Windows. The results of the analysis state that: (1) the work environment has no positive and significant impact on employee performance, (2) work discipline has a positive and significant impact on employee performance, (3) teamwork has a positive and significant impact on employee performance.